Long-lasting hyperopic shift and irregular astigmatism after selective laser trabeculoplasty. Issue 1 (16th January 2021) - Farrokhi, Sanaz; Steinberg, Johannes; Spitzer, Martin S.; Linke, Stephan J.
Abstract : We report a rare side effect after routine selective laser trabeculoplasty (SLT), which remained until the last visit, 36 months after the procedure. A patient with no pathological findings after the procedure, such as corneal haze or corneal edema, complained about blurred vision 7 weeks after undergoing uneventful SLT. Refractive changes that topographically displayed as a decrease in the total corneal power from 41.29 diopters (D) to 36.38 D and the development of an irregular corneal astigmatism were observed. Clinically, these corneal changes lead to a massive hyperopic shift with a decrease in the spherical equivalent from −7.75 to +2.25 and a decrease in the corrected distance visual acuity to 20/200. The patient regained a full visual acuity of 20/20, and anisometropia could be treated with rigid gas-permeable contact lenses (RGPCLs). Although refractive changes after SLT are underreported, ophthalmologists should be aware of this side effect and its effective symptomatic treatment with RGPCLs.